Feasibility Study on the Value of Self-Help Housing Stimulus Assistance to Achieve Liveable Houses for Communities in East Java Province - Wardiha, Made Widiadnyana (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2025)
Self-Help Housing Stimulus Assistance (BSPS) is a program that renovates unlivable houses with government funds of IDR20,000,000, with the remaining funds provided by the program recipient’s self-help funds. The assistance value has been set since 2020, but, aside from inflation, the community also stated that it was insufficient. Therefore, a study was conducted to assess the adequacy of assistance value by sampling 195 BSPS recipients across nine regencies/cities in East Java Province. The results showed that the BSPS house renovation costs were influenced by the recipient's self-help value, averaging IDR11,583,677. Although the average self-help value is quite large, the BSPS assistance of IDR 20,000,000 still needs to be increased to between IDR 21,000,000 and IDR 26,000,000. An increase in assistance value from IDR1,000,000 to IDR6,000,000 will provide relief for the community through self-help and optimize the amount of assistance and community self-help to meet the needs for livable housing specifications. The results of this study can also inform a re-examination of the design and budget plan for simple houses for the community, especially those with low incomes, to ensure they remain liveable and affordable.